Pengaruh Job Insecurity terhadap Work Engagement pada Tenaga Kependidikan Honorer di Sekolah - Lies Ramadhanty; Anna Rozana (UNISBA Press, 2023)
Abstract. Engaged employees are very important organizational asset because it relates to employee performance and organizational management, that is the reason why organizations need employees that be able to invest in work (Bakker & Demerouti, 2018; Knight et al., 2017; Simpson, 2009). Several studies state that job insecurity has a strong influence on work engagement on employees (Bosman et al., 2005a; Wang et al., 2015). This study aims to determine the effect of job insecurity on the work engagement of honorary education staff at schools in District B that related to the existence of a Government Regulation which states that on November 23, 2023 there will be dismissal of honorary staff. This research use quantitative method with a causality research design using multiple regression techniques. The measurement scale uses the job insecurity scale (Ashford et al., 1989) and UWES-9 (Schaufeli & Bakker, 2004). Job insecurity give impact on work engagement of honorary school education staff in district B by 56% and the remaining 44% is influenced by other factors that not examined in this study. Job insecurity component that has the greatest influence on work engagement is the perceived threat to a total job component by 14.09%. Keywords: Job Insecurity, Work Engagement, Honorary Education Staff at School Abstrak. Karyawan yang engage merupakan aset organisasi yang sangat penting karena berkaitan dengan performance karyawan dan manajemen organisasi sehingga organisasi memerlukan karyawan yang mampu berinvestasi pada pekerjaan (Bakker & Demerouti, 2018; Knight et al., 2017; Simpson, 2009). Beberapa penelitian menyatakan bahwa job insecurity mempunyai pengaruh yang kuat dengan work engagement pada karyawan (Bosman et al., 2005; Wang et al., 2015). Penelitian ini bertujuan untuk mengetahui pengaruh job insecurity terhadap work engagement pada tenaga kependidikan honorer di sekolah pada Kabupaten B berkaitan dengan adanya Peraturan Pemerintah yang menyatakan bahwa pada tanggal 23 November 2023 mengenai pemberhentian tenaga honorer. Metode penelitian yang digunakan adalah kuantiatif dengan desain penelitian kausalitas menggunakan teknik multiple regression. Skala pengukuran menggunakan Job Insecurity Scale (Ashford et al., 1989) dan UWES-9 (Schaufeli & Bakker, 2004). Job insecurity memberikan pengaruh terhadap work engagement pada tenaga kependidikan honorer sekolah di kabupaten B sebesar 56% dan sisanya yaitu 44% dipengaruhi oleh faktor lain yang tidak diteliti dalam penelitian ini. Komponen job insecurity yang memberikan pengaruh paling besar terhadap work engagement adalah komponen perceived threat to a total job sebanyak 14.09%. Kata Kunci: Job Insecurity, Work Engagement, Tenaga Kependidikan Honorer